ANALISIS PERANGKAT PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI KELAS III SEKOLAH DASAR NEGERI 66 PONTIANAK KOTA - Novia Alfionita Novia Alfionita; Siti Halidjah; Suparjan Suparjan (Universitas Tanjungpura, 2020)
AbstractThe aim of this research was describe the Analysis of IPS Learning Devices in Grade III of Public Elementary School 66 Pontianak City. The method used in this research was by descriptive method of qualitative research type. The data source in this study was in the form of a learning device document in the form of learning device plan (RPP) compiled by grade III teachers who teach in the elementary school of pontianak city namely the elementary school of 66 pontianak city. The results showed that there were several components of the study implementation design that have been written or not written according to Permendiknas Number 41 year 2007. Teaching materials submitted by teachers were in accordance with the purpose of learning and teaching materials that were presented easily to be understood in accordance with the student's credible. The form of evaluation given by the teacher was in accordance with the competency achievement indicator and contains rubric assessment according to the reference aspect that will be achieved by the learner.Keywords: Analysis, Learning Tools, Learning Social Knowledge